Contradictions in the Chilean Government’s Immigration Policy (2018-2022) - Cociña-Cholaky, Martina (2022)
Under the slogan of “putting the house in order”, the government of Sebastián Piñera, since his presidential inauguration in 2018, has imposed various requirements on human mobility, which have hindered the entry and regular stay of groups such as Haitians and Venezuelans. These measures have been accompanied by a commitment to the militarization of the northern border and the mediatization of expulsions, along with a rhetoric that dichotomizes displacements into positive/negative, according to their administrative situation, thus conditioning the rights of migrants. This paper examines, from the paradigm of migration governance and through a documentary analysis, the Chilean migration policy from 2018 to 2022, investigating from a qualitative and exploratory approach the main measures implemented and the rhetoric used. It is concluded that in this presidential period a policy has been intensified that, through a human rights narrative, restricts certain flows, increasing irregularity and the precariousness of the crossings, consequences that contradict the premise of “orderly, safe and regular migration” on which the government administration is based. This dynamic has been strongly expressed in the Tarapacá Region, a territory that has become the epicenter of the migratory situation.